Essentials of Business Law - Ewan MacIntyre (UK Pearson, 2018)
Essentials of Business Law is well regarded for its clear yet succinct exposition of core principles and key cases across the essential legal topics relevant to business students. This new edition has been significantly updated and deals fully and comprehensively with the Consumer Rights Act 2015.
Keywords: Business law; Commercial law